1998
DOI: 10.1375/136905298320566285
|View full text |Cite
|
Sign up to set email alerts
|

Feelings and the need for information and counselling of expectant parents of twins

Abstract: I n thi s study, expectant par ents of tw i ns w er e questi oned about thei r feel i ngs and need for information and counselling on the parenting of twins. Data were obtained from self-rating questi onnai r es and an i nter vi ew w i th the expectant mother. Fr om the r esul ts i t i s ar gued that expectant parents of twins need specific information and counselling about the medi cal , emoti onal and parenting issues of having twins. Guidelines for organising this counselling are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…For many parents, this will be their first pregnancy and some will be unsure of what they need to learn and what questions to ask about infant feeding (Mariano & Hickey, 1998;Nys et al, 1998). Expectations about breastfeeding may be high, particularly if this is a long awaited pregnancy.…”
Section: Supporting Evidence and Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…For many parents, this will be their first pregnancy and some will be unsure of what they need to learn and what questions to ask about infant feeding (Mariano & Hickey, 1998;Nys et al, 1998). Expectations about breastfeeding may be high, particularly if this is a long awaited pregnancy.…”
Section: Supporting Evidence and Guidelinesmentioning
confidence: 99%
“…The stress associated with multiple pregnancy and parenting multiples may be overwhelming and interfere with a parent's ability to learn about breastfeeding two or more (Mariano & Hickey, 1998;Sollid et al, 1989). A Flemish study of 62 couples expecting twins found that the parents used a variety of sources such as the literature and other parents of twins to learn about multiples-specific feeding issues (Nys et al, 1998). Twenty-six per cent of the participants stated that they would have liked to receive more information.…”
Section: Supporting Evidence and Guidelinesmentioning
confidence: 99%
“…La plupart des études évoque la grossesse multiple comme une épreuve marquée de difficultés physiques et psychologiques [6][7][8][9]. Toute grossesse s'accompagne de modifications physiologiques qui sont en général accentuées en cas de grossesse multiple.…”
Section: Introductionunclassified
“…Several studies have reported that mothers of multiples feel ill‐prepared for unexpected complications around the birth, and for the impact of parenting more than one infant . Mothers of multiples also report a lack of information and support during pregnancy and after the birth . Traditional antenatal education classes may be unsuitable for parents of multiples, as they focus predominately on singleton vaginal delivery.…”
Section: Introductionmentioning
confidence: 99%